Peasant livelihoods and geographies of sameness in the Alexander Skutch Biological Corridor, Costa Rica - Espinoza Cisneros, Edgar (2024)
In the rural tropics, many peasant communities have been ensnared for decades in a socioeconomic sameness characterized by an enduring undervalued production, despite these groups being key for food security goals, environmental sustainability, and cultural value. In many rural settings, these disadvantageous conditions have persisted, and although many peasants consequently relinquish their livelihoods, in many other cases they desist from giving up on their ways of life and rather seek strategies to break out of the sameness while conserving their livelihoods and identities. In the Alexander Skutch biological corridor (ASBC) in Costa Rica, the push of peasant families to overcome these adverse conditions has led, among other things, to an entrepreneurship drive manifested through commercialization initiatives and production strategies proposed by self-organized community and producer groups. In this chapter, we examine geographic sameness in peasant communities in the ASBC, what keeps them in a socioeconomic loop, what actions they are taking to break sameness, and discuss their future prospect in the context of sustainability goals.